Radio and Television Programs for National Minorities of the Border Multicultural Region (on the example of Transcarpathia, 1930-1991) - Tolochko, Nataliia (Technium Social Sciences Journal, 2020)
The article deals with the acute problems of the origin and development of radio and television programs for national minorities within the border region of Ukraine – Transcarpathia (in pre-Soviet and Soviet periods). The problem under consideration is relevant because of the fact that since the nineteenth century seven states and state entities have changed the territory of Transcarpathia. As representatives of different nationalities, most numerous being Hungarians, Romanians, Russians, Roma, Slovaks, Germans have long lived at this territory, attention has been paid to changing the ethnic picture over the years. The emergence and development of media for national minorities in the pre-Soviet and Soviet periods depended on the political order, ideology of the states including Transcarpathia. Therefore, some ethnic communities did not have radio and television programs in their mother tongue during the USSR period and were granted the right to information only after Ukraine gained independence.